IMPLEMENTASI MANAJEMEN ADMINISTRASI PADA STAF DI KANTOR WALI NAGARI TALANG KOTO PULAI TAPAN - Selfia, Zela; Anwar, Khairul; M. Nurzen, M. Nurzen (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
This research aims to explore the implementation of administrative management among staff at the Wali Nagari Talang Koto Pulai Tapan Office, Pesisir Selatan. The research method used is a qualitative approach with descriptive methods. Data was collected through interviews, observation and documentation. The research results show that the coordination of nagari government institutions in making decisions based on local wisdom has gone quite well. Coordination is carried out by Wali Nagari, Bamus, and KAN. Each institution coordinates according to the problems it faces, including problems related to the administration of nagari government and customs. However, the implementation of coordination activities still has obstacles, especially related to communication factors, institutional ego, and the frequency of coordination meetings. This research provides insight into how administrative management can be implemented effectively in the context of nagari government